Pengaruh Mekanisme Corporate Governance Dan Ukuran Perusahaan Terhadap Manajemen Laba - Launa, Elvia; Respati, Novita Weningtyas (Jurnal Reviu Akuntansi dan Keuangan)
The purpose of this research is to examine the influence of the corporate governance mechanism and firm size concerning to the earnings management. Corporate governance mechanism in this study include managerial ownership, independent commissioner and audit committee. The samples of this research are 7 real estate companies listed in Indonesian Stock Exchange period 2009-2013. This study using a purposive sampling method to determining the number of samples used. The method of analysis on this research is using multiple linear regression analysis. The result of the study shows that managerial ownership, independent commissioner, auditcommittee and firm size are not influence to earnings management. Managerial ownership has no influence to earnings management due to low managerial ownership owned by the samplecompany, while the independent commissioner has no influence because the placement of theindependent commissioner only act to fulfill the formal provisions. Audit committee has noinfluence to earnings management because the member size of audit committee still relativelystandard with the Capital Market Supervisory Agency regulation and firm size has no influenceto earnings management because earnings management’s action not influenced by the firm size.